'Not Just the Ideas of a Few Enthusiasts': Early Twentieth Century Legal Activism and Reformation of the Age of Sexual Consent. (15th March 2017) - Stevenson, Kim
Abstract: In July 1885, a reluctant House of Lords was eventually persuaded to pass the Criminal Law Amendment Bill after three years of intense Parliamentary debate and prompted by W.T. Stead's shocking expose of the Maiden Tribute scandal. The 1885 Act finally, and controversially, settled the age of sexual protection for young girls at 16 years but this threshold would be repeatedly contested over the next four decades. Moral campaigners continually sought to exert pressure on the Home Office to reform what we now recognise as a legal age of consent. But their contradictory demands to impose repressionist measures to punish young girls for sexual immorality while simultaneously lobbying for a more protectionist stance against sexual defilement made any legislative consensus impossible. This article explores and teases out the associated socio-legal complexities of such contradictions which, somewhat ironically, served as a stark rehearsal for the passage of the Criminal Law Amendment Act 1922. An Act which did no more than simply reiterate the 1885 determination that 16 years should be the age of consent, a provision that has endured well into the twenty-first century.